Internet... the final frontier: an ethnographic account: exploring the cultural space of the Net from the inside - Sabine Helmers; Ute Hoffmann; Jeanette Hofmann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
The research project The Internet as a space for interaction, which completed its mission in Autumn 1998, studied the constitutive features of network culture and network organisation. Special emphasis was given to the dynamic interplay of technical and social conventions regarding both the Net's organisation as well as its change. The ethnographic perspective chosen studied the Internet from the inside. Research concentrated upon three fields of study: the hegemonial operating technology of net nodes (UNIX) the network's basic transmission technology (the Internet Protocol IP) and a popular communication service (Usenet). The project's final report includes the results of the three branches explored. Drawing upon the development in the three fields it is shown that changes that come about on the Net are neither anarchic nor arbitrary. Instead, the decentrally organised Internet is based upon technically and organisationally distributed forms of coordination within which individual preferences collectively attain the power of developing into definitive standards.
Keywords: 330; Internet; Kulturpsychologie; Welt